Cloning and nucleotide sequence of luxR, a regulatory gene controlling bioluminescence in Vibrio harveyi. - Showalter, R E (1990)
Mutagenesis with transposon mini-Mulac was used previously to identify a regulatory locus necessary for expression of bioluminescence genes, lux, in Vibrio harveyi (M. Martin, R. Showalter, and M. Silverman, J. Bacteriol. 171:2406-2414, 1989). Mutants with transposon insertions in this regulatory locus were used to construct a hybridization probe which was used in this study to detect recombinants in a cosmid library containing the homologous DNA. Recombinant cosmids with this DNA stimulated expression of the genes encoding enzymes for luminescence, i.e., the luxCDABE operon, which were positioned in trans on a compatible replicon in Escherichia coli. Transposon mutagenesis and analysis of the DNA sequence of the cloned DNA indicated that regulatory function resided in a single gene of about 0.6-kilobases named luxR. Expression of bioluminescence in V. harveyi and in the fish light-organ symbiont Vibrio fischeri is controlled by density-sensing mechanisms involving the accumulation of small signal molecules called autoinducers, but similarity of the two luminescence systems at the molecular level was not apparent in this study. The amino acid sequence of the LuxR product of V. harveyi, which indicates a structural relationship to some DNA-binding proteins, is not similar to the sequence of the protein that regulates expression of luminescence in V. fischeri. In addition, reconstitution of autoinducer-controlled luminescence in recombinant E. coli, already achieved with lux genes cloned from V. fischeri, was not accomplished with the isolation of luxR from V. harveyi, suggesting a requirement for an additional regulatory component.